FRI0242 Disease Burden of Ankylosing Spondylitis in Taiwan: A Population-Based Analysis. (9th June 2015) - Wang, B.C.; Tang, C.-H.; Furnback, W.; Ney, J.P.; Yang, Y.-W.; Fang, C.-H.; Chen, W.-S.
Abstract : Background: Ankylosing spondylitis (AS) is a form of arthritis that affects the spine. The spinal joints are inflamed causing severe pain and discomfort. Severe effects of AS can include new bone formation on the spine causing immobility. It is associated with decreased quality-of-life in its patients, and pharmacological and non-pharmacological treatments are available. Objectives: This research aims to estimate the economic burden of AS in Taiwan. Methods: The National Health Insurance Research Database (NHIRD), a claims-based dataset encompassing 99% of Taiwan's population, was utilized. The costs and quantities of the direct economic burden were calculated based on 2011 data of NHIRD. We identified AS patients and a control cohort matched 1:4 on demographic and clinical covariates to calculate the incremental cost related to AS. We used a micro-costing approach for direct health care costs by estimating the quantities and prices of cost categories. Direct costs included surgeries, hospitalizations, medical devices and materials, lab tests, and drugs. Costs were presented in 2014 USD (1 USD =30.09 TWD). Results: A total of 12, 783 AS patients were included in the database with incremental total direct cost of $18, 002, 445 due to AS. This resulted in an average incremental direct cost of $1, 408 per AS patient. Within direct costs, the largest burdens were associated with medication ($15, 884, 949; 88.24%), lab tests ($1, 432, 333; 7.96%), surgery ($329, 471; 1.83%), medical devices and materials ($305, 609; 1.7%) and ward usage ($50, 084; 0.28%). Medications are broken down by class in table 1 . Conclusions: The economic burden of AS in Taiwan is driven by medication costs and lab tests. Efficient management of AS may reduce the utilization and treatment costs associated with the disease. Disclosure of Interest: B. C. Wang Grant/research support from: Pfizer, C.-H. Tang Grant/research support from: Pfizer, W. Furnback Grant/research support from: Pfizer, J. P. Ney: None declared, Y.-W. Yang Employee of: Pfizer Taiwan, C.-H. Fang Employee of: Pfizer Taiwan, W.-S. Chen: None declared